2005
DOI: 10.1143/jjap.44.8231
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Density Oxygen Plasma Posttreatment on Field Emission Properties of Carbon Nanotube Field-Emission Displays

Abstract: The effects of oxygen plasma posttreatment (PPT) on the morphology and field emission properties of carbon nanotube (CNT) arrays grown on silicon substrates are proposed and experimental results are reported. Oxygen PPT led to an enhancement in the emission properties of CNTs, which showed an increase in total emission current density and a decrease in turn-on field after plasma treatment. Scanning electron microscopy (SEM) images showed reduced densities of the CNTs, which resulted in a decrease of the screen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
12
1
Order By: Relevance
“…This work details the use of an oxygen plasma etch to dramatically improve device yield by reversing shorting of the gate after CNT synthesis -a common time for a short to develop. The use of different plasma treatments on CNTs are commonly used to improve FE performance [19][20][21][22], by introducing defects as FE sites [23] and reducing screening by neighboring CNTs [24,25]. However, no published work seems to detail the use of a plasma etch to reverse shorting of a Spindt type CNT electron source.…”
Section: Introductionmentioning
confidence: 99%
“…This work details the use of an oxygen plasma etch to dramatically improve device yield by reversing shorting of the gate after CNT synthesis -a common time for a short to develop. The use of different plasma treatments on CNTs are commonly used to improve FE performance [19][20][21][22], by introducing defects as FE sites [23] and reducing screening by neighboring CNTs [24,25]. However, no published work seems to detail the use of a plasma etch to reverse shorting of a Spindt type CNT electron source.…”
Section: Introductionmentioning
confidence: 99%
“…Many schemes have been implemented worldwide for the minimisation of shielding effect such as by varying the height and spacing of vertically aligned CNTs [19], controlling the tip densities of CNTs [20]. There are other reports like plasma treatment [21,22], wet etching [23] and HF acid treatment [24] of grown CNTs for improving field emission current. R Seelaboyina et al have proposed multistage growth [25] while J. Hu et al tried onion shaped tips [26] for enhancing the current density.…”
Section: Introductionmentioning
confidence: 99%
“…15͒ has been used to alter the FE properties of CNT arrays by removing surface amorphous carbon impurities, 16,17 introducing defects, 15 and by modifying the work function of the surface of the CNTs.…”
mentioning
confidence: 99%
“…15͒ has been used to alter the FE properties of CNT arrays by removing surface amorphous carbon impurities, 16,17 introducing defects, 15 and by modifying the work function of the surface of the CNTs. 12 Previous work has shown that O 2 impurities etch the base of the CNTs during FE characterization due to large contact resistances between the substrate and CNTs, resulting in an increase in threshold field.…”
mentioning
confidence: 99%
See 1 more Smart Citation